Employability of adult education postgraduate students in university of Ibadan, Nigeria: opportunities and threats (2016)
There is a growing interest in employability among postgraduate students in University of Ibadan. The study aimed at the opportunities that are available for postgraduate students of the department of adult education. It found out that postgraduate students lack requisite skills in setting career goal for themselves and consequently suffer from lack of focus despite the efforts of the University